Performance of corporate sector, 1996-97 - Dash, J. (1999)
An analysis of the performance of the corporate sector in 1996-97 indicates that there is scope for expanding equity capital and reducing dependency on capital based on loans and borrowings. - Reproduced
Keywords: Enterprises - India; Enterprises